1997
DOI: 10.1016/s0014-5793(97)01145-9
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial cytochrome c oxidase subunit IV is phosphorylated by an endogenous kinase

Abstract: This study was undertaken to identify novel mitochondrial membrane proteins that are potential targets for phosphorylation. Mitochondrial membranes were incubated in the presence of [y-32 P!ATP and the Triton X-114 extractable protein was subjected to ion-exchange and polyacrylamide gel chromatography to purify a major phosphorylated protein of approximately 17000 Da. The determined peptide sequence of the purified phosphoprotein corresponded to a segment of cytochrome c oxidase subunit IV, an inner membrane p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 56 publications
0
54
0
Order By: Relevance
“…The CcO activity is substantially altered in mammalian cells exposed to acute hypoxia and tissues subjected to ischemia-reperfusion (10,11,24,25,40). We (40) and others (5,28,47) have previously shown that cAMP-mediated phosphorylation plays a role in the regulation of CcO activity. In a previous study (40) we subjected our Langendorff-perfused rabbit hearts to varying degrees of global and regional ischemia.…”
Section: Discussionmentioning
confidence: 81%
“…The CcO activity is substantially altered in mammalian cells exposed to acute hypoxia and tissues subjected to ischemia-reperfusion (10,11,24,25,40). We (40) and others (5,28,47) have previously shown that cAMP-mediated phosphorylation plays a role in the regulation of CcO activity. In a previous study (40) we subjected our Langendorff-perfused rabbit hearts to varying degrees of global and regional ischemia.…”
Section: Discussionmentioning
confidence: 81%
“…Increasing reports over the past few years suggest a direct regulation of mitochondrial activity by phosphorylation events in several cell types, in which some classical cytosolic kinases are found in mitochondria [32][33][34][35] acting on different subunits of the respiratory chain complexes. [36][37][38][39][40][41] We cannot exclude a direct regulation of mitochondrial activity by sodium tungstate. If this is the case, sodium tungstate would open up a new Dual effects of tungstate on adipocyte biology MC Carmona et al…”
Section: Discussionmentioning
confidence: 99%
“…In hypoxia and myocardial ischemia conditions, mitochondrial dysfunction was shown to be associated with loss of CcO activity (28,31,81), which was associated with selective loss of mitochondrion-encoded subunit I that houses the heme a/a3 and copper centers, and nuclear gene-coded subunits IVI1 and Vb (82)(83)(84). Protein phosphorylation was implicated in these losses (28,31,(85)(86)(87). Interestingly, our results show the loss of the same two nucleus-encoded subunits (IVI1 and Vb) in alcohol-treated Mt ϩϩ cells and also in livers of rats fed with alcohol for Ͻ6 weeks (Fig.…”
Section: Discussionmentioning
confidence: 99%